2004
DOI: 10.4049/jimmunol.173.9.5398
|View full text |Cite
|
Sign up to set email alerts
|

β-Defensin-2 Expression Is Regulated by TLR Signaling in Intestinal Epithelial Cells

Abstract: The intestinal epithelium serves as a barrier to the intestinal flora. In response to pathogens, intestinal epithelial cells (IEC) secrete proinflammatory cytokines. To aid in defense against bacteria, IEC also secrete antimicrobial peptides, termed defensins. The aim of our studies was to understand the role of TLR signaling in regulation of β-defensin expression by IEC. The effect of LPS and peptidoglycan on β-defensin-2 expression was examined in IEC lines constitutively or transgenically expressing TLRs. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
227
1
9

Year Published

2005
2005
2011
2011

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 322 publications
(250 citation statements)
references
References 61 publications
13
227
1
9
Order By: Relevance
“…These results indicate that NF-B and, to a lesser degree, AP-1 play a critical role in the regulation of the NOD2-mediated hBD-2 induction. These results are consistent with previous reports demonstrating an important role of NF-B for induction of hBD-2 in epithelial cells upon stimulation with bacteria or bacterial products (23,25,26,(45)(46)(47).…”
Section: Discussionsupporting
confidence: 83%
“…These results indicate that NF-B and, to a lesser degree, AP-1 play a critical role in the regulation of the NOD2-mediated hBD-2 induction. These results are consistent with previous reports demonstrating an important role of NF-B for induction of hBD-2 in epithelial cells upon stimulation with bacteria or bacterial products (23,25,26,(45)(46)(47).…”
Section: Discussionsupporting
confidence: 83%
“…We have recently demonstrated that TLR4-and TLR2-dependent pathways can stimulate ␤-defensin-2 expression by intestinal epithelial cells (36). These data suggest that, like Paneth cells, intestinal epithelial cells respond to PAMPs by secreting antimicrobial peptides.…”
Section: Secretion Of Anti-microbial Peptidesmentioning
confidence: 90%
“…Epithelial cells on intestinal villi act as sensors of the luminal environment, and intestinal epithelial cell monolayers in vitro can release inflammatory cytokines in response to pathogen attachment and invasion (1,2). Intestinal epithelial cells express a variety of potential sensing receptors, including TLRs (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19), that may play a role in mucosal responses to microbial components.…”
mentioning
confidence: 99%